Thermal characterization of Malaysian biomass via thermogravimetric analysis - Vekes, Balasundram; Noorhaza, Alias; Norazana, Ibrahim; Rafiziana, Md. Kasmani; Ruzinah, Isha; Mohd. Kamaruddin, Abd. Hamid; Hasrinah, Hasbullah (UTM Press, 2018)
In this work, thermal degradation behavior of six local biomasses such as empty fruit bunch, rice husk, coconut pulp, saw dust, coconut shell, and sugarcane bagasse in Malaysia via pyrolysis was studied. The pyrolysis process was carried out from 25 to 700 °C under nitrogen atmosphere flowing at 150 ml/min via a thermogravimetric analyzer. The effect of biomass type was investigated on pyrolysis behavior. The particle size of biomass was in the range of 0.3 ≤ dp1 < 0.5 mm, whereas the heating rate was fixed at 80 °C/min. The thermogravimetric analysis (TGA) data were divided into three phases of degradation: moisture evolution, hemicellulose-cellulose degradation, and lignin degradation. The results showed that all biomass samples degraded between 25 and 170 °C in Phase I of moisture evolution. Among the biomass samples, coconut pulp achieved the highest mass loss (81.9%) in Phase II of hemicellulose-cellulose degradation. Lignin in all biomass samples gradually degraded from 450 to 700 °C in Phase III of lignin degradation. This study provides an important basis in understanding the intrinsic thermochemistry behind degradation reactions.